Feasibility of Local Commodities on Peatlands - Resti Salmayenti; Muhammad Sugihartono; Elham Sumarga; Fauziah Nur; Aan Aryanti Sandra (Research Centre of Inorganic Materials and Complexs, 2022)
Indonesian peat ecosystem, generally managed for protection and cultivation functions, contributes to providing economic benefits to the local community through agricultural practices. This study aims to evaluate the feasibility of local commodity agriculture (coffee, areca, coconut, and pineapple) on peatland from social, ecological, and economic perspectives using descriptive and quantitative approaches in Mendahara-Batanghari, Jambi. Data was collected from interviews of 60 farmers in two villages with three types of farms, including monoculture and polyculture of commodities. The results of this study showed that socially, farmers still have difficulty with access and infrastructures. Coconut, areca, and coffee are popular among the smallholders because of land suitability, low maintenance, and high selling price. From an ecological perspective, intercropping on polyculture farms is able to store more carbon with a high density of biomass than on monoculture farms. Generally, the carbon emissions of local commodity farms are lower than other types of plantations, such as oil palm and rubber plantations. Lastly, from an economic perspective, local commodity farming in the study area is feasible based on analyses of net present value, benefit cost ratio, and internal rate of return. Polyculture farms provide higher benefits compared to monoculture land. The income is considered sufficient for standard living needs, and there is potential to increase the revenue by developing and optimising processing product industries.